Changes in stiffness of the extracellular and pericellular matrix in the anulus fibrosus of lumbar intervertebral discs over the course of degeneration - Höflsauer, Sebastian; Bonnaire, Florian Christof; Bamberger, Charlotte Emma; Danalache, Marina; Feierabend, Martina; Hofmann, Ulf Krister (Frontiers in Bioengineering and Biotechnology, 2022)
Analogous to articular cartilage, changes in spatial chondrocyte organisation have been proposed to be a strong indicator for local tissue degeneration in the intervertebral disc (IVD). While a progressive structural and functional degradation of the extracellular (ECM) and pericellular (PCM) matrix occurs in osteoarthritic cartilage, these processes have not yet been biomechanically elucidated in the IVD. We aimed to evaluate the local stiffness of the ECM and PCM in the anulus fibrosus of the IVD on the basis of local chondrocyte spatial organisation. Using atomic force microscopy, we measured the Young’s modulus of the local ECM and PCM in human and bovine disc samples using the spatial chondrocyte patterns as an image-based biomarker. By measuring tissue from 31 patients and six bovine samples, we found a significant difference in the elastic moduli (E) of the PCM in clusters when compared to the healthy patterns single cells (p = 0.029), pairs (p = 0.016), and string-formations (p = 0.010). The ECM/PCM ratio ranged from 0.62–0.89. Interestingly, in the bovine IVD, the ECM/PCM ratio of the E significantly varied (p = 0.002) depending on the tissue origin. Overall the reduced E in clusters demonstrates that cluster formation is not only a morphological phenomenon describing disc degeneration, but it marks a compromised biomechanical functioning. Immunohistochemical analyses indicate that collagen type III degradation might be involved. This study is the first to describe and quantify the differences in the E of the ECM in relation to the PCM in the anulus fibrosus of the IVD by means of atomic force microscopy on the basis of spatial chondrocyte organisation.